Inclusion: legal aspects of reinforcing and implementing the constitutional right to educate children with special needs in Russia - Kazmina, Ekaterina A. (Journal of the Belarusian State University. Law, 2022)
The article is devoted to the problem of finding a balance in the implementation of inclusive education and general education in specialised (correctional) educational organisations. Inclusive education, despite its undoubted qualities, high accuracy of assessment in terms of the socialisation of the individual, can be especially true in terms of the quality of education due to the possibility of providing personalised learning and providing highly qualified personnel with the skills to work with children with a high level of learning ability. Meanwhile, the negative attitude towards specialised institutions that has developed in society requires rethinking, in which it is difficult to overestimate the role of state institutions. The presence of a choice of forms of education in conditions of careful psychological, medical and pedagogical diagnostics at preschool age can contribute to more effective learning and personal development.